Evaluation of a climbing drum laminate peel test to determine the interlaminar mode I fracture toughness of thin CFRP laminates—Comparison with the standard mode I DCB test and a mandrel laminate peel test proposed by ESIS TC4 - Michel, Silvain; Hauf, Fabian; Brunner, Andreas J. (Frontiers in Materials, 2023)
A recently proposed mandrel laminate peel (MLP) test for quantification of delamination propagation in Fiber-Reinforced Polymer (FRP) composites is compared with a climbing drum laminate peel (CDLP) test, and the standard quasi-static Mode I fracture test with Double Cantilever Beam (DCB) specimens. MLP and CDLP both are applicable to thin laminates, for which the Mode I DCB test is not suitable. MLP and CDLP, however, do not yield delamination initiation values. Delamination propagation resistances from the three tests performed with different types of FRP, one partly and one fully cured epoxy laminate, and one thermoplastic laminate, all with unidirectional fiber lay-up agree within about 20%. Reduction of the diameter of the climbing drum (100 mm for the standard climbing drum peel test for adhesives) indicates a minimum diameter on the order of 50 mm for the CDLP test. Additional tests with selected laminates investigated potential effects of specimen width. It is concluded that FRP laminate specimens 20 mm wide and 180 mm long are sufficient for consistent results from CDLP and MLP tests. The CDLP test yielded less scatter (around 10%), i.e., better repeatability than the MLP (round 13%) and the Mode I DCB test (around 17%). Hence, the CDLP test is considered advantageous for industrial application, also due to the simplicity of the test set-up and of the data analysis.